2010
DOI: 10.1002/dvdy.22419
|View full text |Cite
|
Sign up to set email alerts
|

A direct role for Wnt8 in ventrolateral mesoderm patterning

Abstract: Vertebrate dorsoventral patterning requires both Wnt8 and BMP signaling. Because of their multiple interactions, discerning roles attributable specifically to Wnt8 independent of BMP has been a challenge. For example, Wnt8 represses the dorsal organizer that negatively regulates ventral BMP signals, thus Wnt8 loss-of-function phenotypes may reflect the combined effects of reduced Wnt8 and BMP signaling. We have taken a loss-of-function approach in the zebrafish to generate embryos lacking expression of both Wn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
26
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 50 publications
4
26
0
Order By: Relevance
“…Wnt8a (Lekven et al, 2001;Hikasa and Sokol, 2013;Baker et al, 2010) signaling plays additional roles during mesodermal development. During gastrulation, Wnt8a signaling regulates the expression of several mesodermal ventrolateral markers required for the maintenance and proliferation of non-axial mesoderm (Baker et al, 2010;Ramel et al, 2005). In addition, Wnt signaling originating in the lateral mesodermal precursors acts on anterior neuroectoderm to posteriorize the neural tissue (Erter et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Wnt8a (Lekven et al, 2001;Hikasa and Sokol, 2013;Baker et al, 2010) signaling plays additional roles during mesodermal development. During gastrulation, Wnt8a signaling regulates the expression of several mesodermal ventrolateral markers required for the maintenance and proliferation of non-axial mesoderm (Baker et al, 2010;Ramel et al, 2005). In addition, Wnt signaling originating in the lateral mesodermal precursors acts on anterior neuroectoderm to posteriorize the neural tissue (Erter et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In zebrafish embryos, maternal Wnt/β-catenin signaling promotes the dorsal organizer formation before gastrulation (Bellipanni et al, 2006;Schneider et al, 1996). By contrast, zygotic Wnt/β-catenin signaling promotes ventrolateral mesodermal development to limit the organizer after the onset of gastrulation, and thereafter promotes posterior neural development (Baker et al, 2010;Erter et al, 2001;Lekven et al, 2001;Ramel et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…We evaluated whether Mcc can inhibit β-catenin-dependent activation of the −0.8 kb Xenopus Siamois luciferase reporter, and found that Mcc overexpression has no effect on reporter activation -neither synergy nor inhibition -upon co-injection of mRNA encoding either the canonical Wnt8 ligand, which normally suppresses dorsal organizer genes and patterns ventrolateral mesoderm, or its effector β-catenin (Baker et al, 2010) (supplementary material Fig. S2E).…”
Section: Introductionmentioning
confidence: 99%